Environmental Leadership of Ecopesantren Supports Sustainable Development Goals - Muhamad Taufik Bintang Kejora; Aan Komariah; Endang Herawan; Asep Sudarsyah (Didaktika: Jurnal Kependidikan, 2025)
This study aims to explore how environmental leadership in Islamic boarding schools plays a role in supporting the achievement of the Sustainable Development Goals (SDGs) through the integration of Islamic spiritual values, sustainable education, and technological innovation. The global environmental crisis and the urgency of implementing the SDGs demand educational innovations that can combine ecological awareness, spirituality, and environmentally friendly technology. Pesantren, as a community-based Islamic educational institution, has great potential in shaping the character of students who are not only religious but also care about environmental sustainability. However, research on the role of pesantren in supporting the sustainability agenda is still limited. Using a qualitative approach and an exploratory descriptive design, this study collects data through semi-structured interviews, direct observation, and documentation involving leaders, teachers, and students at Al Ashriyyah Nurul Iman Ecopesantren. The results of the study show that environmental leadership in Islamic boarding schools contributes to SDG3 through organic agriculture and ecology-based sanitation, SDG4 with a spiritual and environment-based curriculum, and SDG5 through women's empowerment in environmental leadership. In addition, SDG6 and SDG7 are realized with environmentally friendly technologies such as biogas, solar panels, and reverse osmosis systems, while SDG17 is strengthened by global and local collaborations. Although this study has limitations in geographical scope and long-term impact exploration, the results enrich the discussion on the integration of environmental education in pesantren and provide recommendations for the Islamic education system in supporting sustainable development.